2014
DOI: 10.3758/s13421-014-0441-y
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for feedback helps if you want to know the answer: the role of curiosity in the delay-of-feedback benefit

Abstract: When participants answer a test question and then receive feedback of the correct answer, studies have shown that the feedback is more effective when it is delayed by several seconds rather than provided immediately (e.g., Brackbill & Kappy, Journal of Comparative and Physiological Psychology, 55, 14-18, 1962; Schroth, Contemporary Educational Psychology, 17, 78-82, 1992). Despite several demonstrations of this delay-of-feedback benefit, a theoretical explanation for this finding has not yet been developed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
(57 reference statements)
7
27
0
Order By: Relevance
“…Considering first the younger participants, our findings replicate on a large sample the results of previous studies that showed an enhancing effect of curiosity on the recall of trivia facts (Kang et al, 2009;Gruber et al, 2014;Mullaney et al, 2014;Marvin & Shohamy, 2016). One possible explanation for the observed curiosity-driven memory benefit is that curiosity exerts its effects on memory through reward-related mechanisms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Considering first the younger participants, our findings replicate on a large sample the results of previous studies that showed an enhancing effect of curiosity on the recall of trivia facts (Kang et al, 2009;Gruber et al, 2014;Mullaney et al, 2014;Marvin & Shohamy, 2016). One possible explanation for the observed curiosity-driven memory benefit is that curiosity exerts its effects on memory through reward-related mechanisms.…”
Section: Discussionsupporting
confidence: 86%
“…In a delayed memory test, participants are asked to recall the trivia answers, and their recall accuracy is analysed as a function of prior curiosity judgements. These studies have demonstrated that the more curious participants were about the trivia fact, the higher the likelihood that the answer would be later recalled (Kang et al, 2009;Gruber et al, 2014;Mullaney et al, 2014;McGillivray et al, 2015;Marvin & Shohamy, 2016). Using the same experimental set up, Gruber et al (2014) presented task-irrelevant faces between the trivia question and the answer, and assessed recognition memory accuracy for the faces in a surprise recognition memory test.…”
Section: Introductionmentioning
confidence: 99%
“…Brackbill and Kappy () found that immediate feedback leads to faster immediate acquisition but subjects who received delayed feedback achieved higher grades in subsequent tests. Such a result has been replicated in more recent studies (For example: Mullaney et al , ; Schroth, ).…”
Section: Introductionmentioning
confidence: 59%
“…Studies continue to emerge that support the use of delayed feedback (For example (Butler, Karpicke, & Roediger, 2007;Carpenter & Vul, 2011;Metcalfe et al, 2009;Mullaney, Carpenter, Grotenhuis, & Burianek, 2014;Mullet et al, 2014;Sinha & Glass, 2015;Smith & Kimball, 2010) and research that has considered both short and longer term retention has found that a delay in feedback leads to improved longer term retention of the correct answer. Brackbill and Kappy (1962) found that immediate feedback leads to faster immediate acquisition but subjects who received delayed feedback achieved higher grades in subsequent tests.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if students are complimented for asking questions or attempting a new exploration, they are likely to develop a positive attitude toward being curious and engage in curiosity-related behavior more frequently (Saxe and Stollak 1971). Prompt informative feedback on errors (as opposed to a delayed and simple indication of whether something is right or wrong), such as the timely identification of incongruity and the reasons for an error, can encourage reflexive perception of backward curiosity and lead to in-depth cognitive exploration to rectify their mistakes and to close the knowledge gap (Crooks 1988;Kim et al 2018;Mullaney et al 2014).…”
Section: The Art Of Feedbackmentioning
confidence: 99%